2021
DOI: 10.3389/fctls.2021.790461
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Glutamate Dehydrogenase and Formate Dehydrogenase Yields a Bifunctional Efficient Biocatalyst for the Continuous Removal of Ammonia

Abstract: A novel fusion protein has been rationally designed, combining the hexameric glutamate dehydrogenase from Clostridium symbiosum with the dimeric formate dehydrogenase from Candida boidinii. The former enzyme consumes ammonia for the reductive amination of α-ketoglutarate using NADH, while the latter biocatalyst regenerates continuously the cofactor. This enzymes fusion opens new perspectives for the detection and the removal of ammonia. The bifunctional biocatalyst has been successfully created, expressed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Indeed, the presence of glycine and serine as small polar amino acids has been shown to provide good flexibility and optimal stability in water [23] . A (6x)His‐tag was also fused to the FDH domain for purification purposes as in a previous fusion protein including the CbFDH [19] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, the presence of glycine and serine as small polar amino acids has been shown to provide good flexibility and optimal stability in water [23] . A (6x)His‐tag was also fused to the FDH domain for purification purposes as in a previous fusion protein including the CbFDH [19] …”
Section: Resultsmentioning
confidence: 99%
“…A similar behavior was found in other fusion proteins. The GluDH domain in the GluDH‐FDH protein presented a K M 2‐fold higher than the parental enzymes [19] . Similarly, the PheDH‐FDH‐His fusion protein had 2‐fold higher K M values for the substrates phenylpyruvate and formate than the WT enzymes [31] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been pointed out that the spatial confinement of different biocatalysts operating in parallel or in sequence can drastically reduce diffusion distances of the reagents and thereby accelerate the rate of biocatalytic cascade reactions [2]. Next to co-immobilization of different enzymes [3] or confinement in vesicles [4] also genetically fused enzymes [2,5,6] have been investigated. From these studies it can be concluded that generally, spatial proximity represents an advantage for cascade catalysis as diffusion distances of the individual reagents are reduced.…”
Section: Introductionmentioning
confidence: 99%